Green Intelligent Transportation Systems Proceedings of the 8th International Conference on Green Intelligent Transportation Systems and Safety - Wang, Wuhong; Bengler, Klaus; Jiang, Xiaobei; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
These proceedings collect selected papers from the 8th International Conference on Green Intelligent Transportation Systems and Safety held in Changchun on July 1-2, 2017. The selected works, which include state-of-the-art studies, are intended to promote the development of green mobility and intelligent transportation technology to achieve interconnectivity, resource sharing, flexibility and higher efficiency. They offer valuable insights for researchers and engineers in the fields of Transportation Technology and Traffic Engineering, Automotive and Mechanical Engineering, Industrial and Systems Engineering, and Electrical Engineering.
Advanced Driver Assistance Systems -- Car-2-X Communications -- Green and collaborative driving -- Energy and Emissions Solutions for urban traffic operation -- HMI design, including driver cognitive behaviour, driver distraction -- Intelligent highways and traffic modeling -- Electric vehicles and electricity grids -- Electric energy storage systems and in-transit charging -- Vehicle-Infrastructure Automation -- Modeling and simulation systems for e-Mobility -- Big data in e-Mobility -- Battery technologies for green transportation -- Adaptive mechanisms of electricity grids and charging systems -- Energy and Emissions Solutions for Transit Operation -- Computer Vision for Intelligent Vehicle.
Keywords: Transportation engineering; Traffic engineering; Automotive engineering; Industrial engineering; Production engineering; Transportation Technology and Traffic Engineering; Automotive Engineering; Industrial and Production Engineering